Application of the Realistic Mathematics Education (RME) Approach with a Focus on Social Justice in Teaching and Learning Mathematics - Djam’an, Nurwati (Curtin University, 2014)
Focusing on social justice issues through Realistic Mathematics Education (RME) in this study has been developed. This study informed by action research and grounded theory as the methodology. The study revealed that there are many areas of teacher development demonstrated. This research also showed the effects of the approach upon some variables in mathematics education. Indeed, the finding showed there some evidences that socioeconomic background plays an important role on the implementation of this approach.